Enseignants d’EPS dans un lycée d’élite : le défi de la « lisibilité » - Sarah Pochon (Éducation et Socialisation)
This article focuses on PSE teachers when practicing in a context of excellence and questions the potential constraints on these professionals. The project is to show that PSE teachers in a Parisian elite high school do not encounter "situational" difficulties but face the "legibility" challenge of their discipline. In support of an ethnographic approach and by a socio-ethno-didactic approach, we propose to situate the PSE discipline in its local and social teaching conditions. The results will show that teachers are addressing a socially-favored audience that opposes academic docility to « computational realisme » to the point of confronting teachers with the contrasting representations of students in the discipline. The difficulty of teaching in this context of excellence is to face a challenge: to work for the recognition of the discipline’s identity and its “legibility”.